PENGARUH PEMBERIAN PAKAN KEONG MAS TERHADAP PERTUMBUHAN DAN KELANGSUNGAN HIDUP KEPITING BAKAU SISTEM SINGLE ROOM - Muhammad Agus; HADI Pranggono; Harun Murtadlo (LPPM Universitas Pekalongan, 2011)
AbstractThe Maintenance of mangrove crabs single room system requires the provision of food in quantity and good quality, cheap, on time and deliver high production value. One of the available food for the growth of mangrove crabs in Central Java is the golden apple snail (Pomacea canaliculata), which has a protein content reached 51%. This study aims to determine the effect of feeding fresh golden apple snail with different doses on the growth and survival of mangrove crabs in a single room in the pond system. The study consisted of five treatments fresh golden apple snail fresh feed at a dose of 5.7, 9, 11 and 13% / BW/day) with 5 replications. The experiment conducted at the beginning of mangrove crabs weigh between 80-100 g. Parameters measured include weight gain during maintenance, feed efisiansi, survival and quality of the waters. The results showed, the highest weight gain observed in the treatment of 9% amounting to 92.2 g, while the lowest weight gain observed in the treatment of 5% amounting to 56.6 g. There was no difference in survival in each treatment feed, with the highest survival rate of 100%. The lowest feed efficiency is toun the treatment of feed contained 13% of 41.61%. During the research, the parameters of qualities water in all treatments was within the range for the growth of mangrove crabs. Keywords: Scylla serrata, golden apple snail, growth, survival, feed efficiency